(untitled) (Research, Society and Development, 2021)
The consumption of transgenic foods has increased in the last two decades, from genetic alterations produced in laboratories, through artificial techniques of genetic engineering in plants, animals and microorganisms. Based on this, this work used the literature review methodology to better understand this consumption. According to the articles researched, transgenic organisms do not harm human health, in order to have a lower amount of pesticides in their food, helping in the conservation and production process of their plantations. Concluding that transgenic foods are bringing more benefits than harm to the population.